Karakterisasi Fisik Gel Asam Salisilat Berbasis Pati Sagu Terasetilasi - Mansauda, Karlah Lifie (PHARMACON, 2025)
Salicylic acid gel formulations require a gelling agent that can provide optimal physical stability during storage. This study aimed to characterize the physical properties of salicylic acid gel based on acetylated sago starch as a natural alternative gelling agent. Sago starch was extracted from sago flour with a yield of 87.05%,  and subsequently acetylated, producing modified starch with an acetyl content of 9.46 ± 0.30% and a degree of substitution of 0.39 ± 0.01. Three gel formulations (F1, F2, F3) contained 2% salicylic acid and 6%, 8%, or 10% acetylated starch. Organoleptic properties, homogeneity, pH, adhesiveness, and syneresis were evaluated on days 0 and 30. All formulations exhibited transparent orange color, characteristic salicylic acid odor, semisolid consistency, and stable homogeneity. The pH (5.36–5.91) met topical requirements, adhesiveness increased with starch concentration (≈4.2–5.6 seconds), and syneresis remained low and stable. Acetylated sago starch shows potential as a stable and biocompatible gelling agent for salicylic acid gel.